Gender Gaps in Cognitive and Noncognitive Skills: Roles of SES and Gender Attitudes - Justine Hervé; Subha Mani; Jere R. Behrman; Arindam Nandi; Anjana Sankhil Lamkang; Ramanan Laxminarayan (Institute of Labor Economics (IZA), 2021)
Gender gaps in skills exist around the world but differ remarkably among the high and low-and-middle income countries. This paper uses a unique data set with more than 20,000 adolescents in rural India to examine whether socioeconomic status and gender attitudes predict gender gaps in cognitive and noncognitive skills. We find steep socioeconomic and attitude gradients in both cognitive and noncognitive skills, with bigger effect sizes for the socioeconomic status (SES) gradients. Our results suggest that a sizable improvement in gender attitudes would yield important gains for females, but substantial gains would come only from large improvements in household socioeconomic status. Overall, the household socioeconomic and cultural environment is significantly associated with the gender gaps in both cognitive and noncognitive skills.
Keywords: I21; I25; J13; J16; J24; 330; cognitive skills; noncognitive skills; gender attitudes; gender; India; children